The Gospel of Prosperity in West Africa - Hackett, Rosalind I. J. (Religion and The Transformation of Capitalism: Comparative Approaches, 1995)
This book addresses from a socio-scientific standpoint the interaction of religions and forms of contemporary capitalism. Contributors explore a wide range of interactions between economic systems and their socio-cultural contexts.
paid